National strategic plan for the conservation and use of priority crop wild relatives in Republic of Mauritius - Bioversity International; University of Birmingham; University of Mauritius (2016)
The leaflet provides a summary of the major results achieved in Mauritius within the project: In Situ Conservation and Use of Crop Wild Relatives in three ACP countries of the Southern African Development Community (SADC) region (2014 - 2016), during which a national strategic action plan for in situ conservation of CWR was developed.